Profile of chest trauma patients at B.P. Koirala Institute of Health Sciences, Dharan, Nepal - Sah, Suresh Prasad; Agrawal, R; Agrawal, CS; Koirala, S (Health Renaissance, 2017)
Background: Chest trauma is a major public health problem. It includes injury to chest wall, pleura, tracheobronchial tree, lungs, diaphragm, esophagus, heart and great vessels. It comprises 10-15% of all traumas and 25% of death due to trauma occurs because of chest injury. Chest trauma is seen with increasing frequency in urban hospitals. Methods: A prospective study of all pati with chest injury irrespective of age, sex and mode of injury presenting to BPKIHS emergency were included in this study from 15th March 2007 to 14th March 2008. Results: During the study period of one year total trauma patients presented to emergency were 1524. Out of this 122 patients were of chest injury. It comprises 8% of all trauma patients. Majority of patients belonged to the age group (21-40) years. Out of 122 patients, 57 (46.7%) patients sustained injury due to fall from height and was the commonest cause of trauma in this study followed by road traffic accident which was 38 (31.1%), 15 (12.3%) had physical assault and similar number of 6 patients (4.9%) sustained injury due to gunshot injury and stab injury. Out of 122 patients, 34 (27.9%) patients had associated injury. The most common chest injury was pneumothorax followed by isolated multiple rib fracture, hemothorax, isolated single rib fracture hemopneumothorax, flail chest, subcutaneous emphysema, lung contusion, open pneumothorax and tension pneumothorax. Conclusion: Majority of chest trauma patients were young adults with male preponderance. Blunt trauma chest was most common chest injury. Pneumothorax was the most common chest injury. Majority of patients were managed with tube thoracostomy, analgesics and chest physiotherapy. Health Renaissance 2015;13 (3): 107-113